The interaction between root knot nematodes (Meloidogyne spp.) and soft rot Enterobacteriaceae (Pectobacterium spp.) and their host Solanum tuberosum - Moleleki, Lucy N. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.